Assessing dimethoate contamination in temperate and tropical climates: Potential use of biomarkers in bioassays with two chironomid species - Domingues, Inês
This study was conducted to investigate the potential use of biomarkers in bioassays with chironomids to assess contamination by pesticides in temperate and tropical climates. Two species of midge were studied, the widespread Chironomus riparius and the tropical Kiefferulus calligaster (Kieffer, 1911). Preliminary studies included investigations of the effects of temperature on larval development and the influence of larval age on normal variability of cholinesterase (ChE) and glutathione S-transferase (GST) activities and protein content. In the second phase, the influence of two abiotic factors particularly important in tropical conditions (temperature and oxygen concentration) and of the organophosphorous (OP) insecticide dimethoate on biochemical and conventional endpoints was investigated. Results showed that K colligaster is morphologically and physiologically similar to C riparius and for both, the time of larval development decreases with the increase of temperature. Moreover, 3rd and 4th instars appeared to be the most suitable for biomarkers determinations. ChE activity seems to be valuable biomarker regarding temperature and dissolved oxygen (DO) variations, while some caution should be taken when using GST as an environmental biomarker, since it shows some dependence of these parameters. C riparius was more sensitive to dimethoate than K calligaster suggesting that the use of bioassays with the former species in tropical conditions may overestimate the toxicity of OP pesticides to autochthonous species. When testing sub-lethal effects of dimethoate to C riparius. ChE activity showed to be a very sensitive parameter detecting significant effects at the lowest concentration that caused emergence delay of larvae, suggesting that it is an ecologically relevant parameter. (c) 2007 Elsevier Ltd. All rights reserved.